Design of Custom Storage Rack Based on the Principles of 5S Practices - SELVAM, SOLOMON JAY RAJ; Jamian, Rahim (Progress in Engineering Application and Technology, 2025)
This project addresses storage challenges in the Final Year Project (FYP) committee room at UTHM Pagoh, where poster stands are stored in a disorganized manner. To resolve this, a custom storage rack was designed based on 5S principles (Sort, Set in Order, Shine, Standardize, and Sustain). Data was collected through observations and interviews before and after implementation. The design was analyzed using SolidWorks and built as a prototype, which was implemented in the storage room. The prototype was tested and evaluated for performance, and the results were recorded, showcasing improved storage efficiency, reduced waste, and enhanced accessibility, ultimately benefiting academic and research operations at UTHM.